ПАРАДИГМАЛЬНЫЕ ИЗМЕНЕНИЯ В БИБЛИОТЕКОВЕДЕНИИ: ТЕХНОЛОГИЧЕСКАЯ ПАРАДИГМА И КОНЦЕПЦИЯ ТЕХНОЛОГИЧЕСКОГО МЕНЕДЖМЕНТА В БИБЛИОТЕКЕ (Библиосфера)
The essence of the concept of «paradigm» as applied to librarianship are considered. The basics of forming technological paradigm in the technology management in the library are described.